A Coproduced Traumatic Bereavement Therapeutic Group for Moroccan Adolescents Affected by the Grenfell Tower Fire - Amell El Guenuni; Becky Canton; Fatima El Guenuni; Jeyda Hammad; Rajaa Chellat (Journal of Muslim Mental Health)
There have been increasing calls to coproduce psychological initiatives and services for children and young people to improve access to mental health services and service user experience. This paper outlines the development of an innovative therapeutic group for young people affected by collective trauma and loss who were reluctant to engage with mainstream services following the Grenfell Tower fire. The June 2017 apartment building fire was one of the largest and deadliest to occur in the United Kingdom (UK) in decades, with 72 deaths. The project’s central principle was partnership and coproduction with potential users and offering a culturally appropriate service. Its aim was to meet the mental health and other needs of young people, support them through their bereavement and trauma, and to improve access to mental health services by addressing the barriers they reported. The group approach used community psychology and systemic principles, narrative therapy concepts, creative arts, and collective memorialization. Semi-structured focus groups were conducted with 14 Moroccan-origin adolescents, 13 whom identify as Muslim. A thematic analysis was conducted. Findings indicated the benefits of collective memorialization and therapeutic groups, such as improved emotional expression, recognition of shared Grenfell-related experiences, strengthened social support networks and subjugated narratives, and reduced social isolation and stigma. The evaluation findings indicated that the group’s coproduction and collaboration between statutory services, potential/service users, and community organizations improved community engagement, access to mental health services, and service provision for children and young people from Moroccan and Muslim backgrounds. Note: Any views expressed in this service evaluation are of the authors and do not necessarily reflect the views of their employers.